Cognitive psychology and artificial intelligence: myths and truths - Ramos Franco, Luis Alonso (2014)
The psychology as a science emerged from the human desire of understanding the mind and the behavior. The scientific foundation of this discipline went through complex processes sometimes confusing, in order to be able to determinate which its object of study is and which are the most appropriate methods to address it. In an attempt to scientifically revolutionize this branch of knowledge, cognitive psychology arises in the context of an interdisciplinary work between various sciences, including cybernetics and artificial intelligence, which played a determinant role. Both sciences, cognitive psychology and artificial intelligence, influenced each other. In this paper we will analyze some facts of history and some myths that were created on the concept of “intelligence” and the concept of “revolution”- style Kuhn.